Analysis of Psycholinguistic Approach to Foreign Language Teaching - Begibaeva, Farogat Bakhtiyorqizi (PT. Antis International Publisher, 2024)
In this article, the study of speech behavior in a foreign language by a complex of methods of various sciences is an urgent task of scientific knowledge. The study of the ability to learn foreign languages is carried out using psycholinguistic methods based on contractual forms of communication, taking into account the individual characteristics of speakers, as well as the level of their language culture, semantics and elements of their speech.